Monumental trees and their existence value: the case study of an Italian natural park - A. Asciuto; V. Borsellino; M. D'Acquisto; C.P. Di Franco; M. Di Gesaro; E. Schimmenti (Journal of Forest Science, 2015)
This paper aims to the valuation of the benefits that a local community living in a protected area may perceive with regard to the presence of monumental trees. Financial resources to be destined for protection interventions have been decreasing more and more, with a high risk of losing this natural heritage. A CVM survey was carried out among theMadoniePark(Sicily,Italy) resident households, to evaluate the existence value of monumental trees of the Nature Trail named "Piano Sempria-Piano Pomo", represented by a population of "Giant hollies" and by 7 other individual trees. These are the main results of the CVM survey: the overall response rate was 40%, individual average WTPs were €12.37 for the protection of the holly population and €13.45 for all the monumental trees along the Nature Trail. The median WTPs were respectively €2.00 and €5.00. The aggregate WTP estimates for the Park residents range from a minimum of €10,520.40 to a maximum amount of €83,479.37 depending upon the investigated resource and the statistics considered.